Soil amendments and phosphorus fertilizer increase maize productivity and improve the fertility of acidic soils in Southwestern Ethiopia - Dereje, Getahun; Wogi, Lemma; Tadesse, Desalegn; Sida, Tesfaye Shiferaw; Silva, João Vasco (Research Square, 2025)
Soil acidity is a major constraint to crop production in tropical regions, primarily due to aluminum toxicity and reduced nutrient availability. This challenge is widespread in the highlands of Southwestern Oromia, Ethiopia, where maize is a staple and cash crop. This study evaluated the effects of soil amendments and phosphorus (P) fertilization on post-harvest soil properties, maize physiology, and grain yield during the 2023 and 2024 growing seasons across 14 farmers’ fields in Kersa, Bedele, and Mettu districts. A split-plot design was used with farms as replicates, testing four soil amendments (control, calcitic lime, biochar, vermicompost) and four P rates (0, 15, 30, and 45 kg P ha⁻¹). Calcitic lime and vermicompost markedly improved soil fertility, enhanced maize physiological performance, and increased yields, whereas biochar was less effective. Lime was most effective in raising soil pH, lowering acidity saturation, and increasing P availability, resulting in 38–78% yield gains over the control. Vermicompost also achieved substantial gains (41–66%). Although P fertilization consistently increased yield, its efficiency declined under high acidity saturation. Findings indicate that P response is strongly constrained by soil acidity, and effective management in clay-rich acidic soils requires prior or concurrent soil acidity correction. Integrated strategies combining lime or vermicompost with P fertilization significantly enhanced nutrient availability, maize growth, and productivity. These results highlight the importance of site-specific soil fertility management tailored to acidity levels for improving maize yields in acidic tropical soils.